If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 + 7 = 23 Reorder the terms: -3 + 7 + 2x = 23 Combine like terms: -3 + 7 = 4 4 + 2x = 23 Solving 4 + 2x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2x = 23 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 23 + -4 2x = 23 + -4 Combine like terms: 23 + -4 = 19 2x = 19 Divide each side by '2'. x = 9.5 Simplifying x = 9.5
| 5x-12=-3x+32 | | 18-6-2y=5-2y | | 7f*7=8*7 | | 3(2b+4)=36 | | 2x^3+8=62 | | 8m+7-5m=37 | | 8p-11p=36 | | x^2-3x+3= | | 1y-y=4+5y | | -82=53+-5t | | 32-3(4y-9)-2y=-11 | | 5s-12=-19+4s | | 329.99=25.75+23.50x | | y=-4+20 | | 9x-5x=-32 | | 9=m*2 | | 6(2+k)=3(3-k) | | 4y-20=-23+y | | 5x-4=8+3x | | 41-2m=2+m | | 2(x-5)=24 | | 9(x-2)+4=31 | | 11u=u+14 | | 4y-20=-23+4 | | 3x^2-16y^2+2xy=0 | | 4(.5x-2)=0 | | 7x+14=5x+20 | | 3(6e+3f-2f)= | | (3x+7)(3x^2-25x+42)=0 | | (28.25+18)x=(19.85+32)x | | 8p-13=1+p | | 8(m-3)=56 |